Human Resource Capacity of The Indonesian National Police in Law Enforcement: A Case Study at The Criminal Investigation Unit of Polrestabes Semarang - Darwin Tamba; Arthur Josias Simon Runturambi; David Ronald Tairas (Greenation International Journal of Economics and Accounting, 2026)
This study examines the human resource (HR) capacity of the Criminal Investigation Unit (Satreskrim) of Polrestabes Semarang in law enforcement, encompassing four analytical dimensions: technical competence, integrity, professionalism, and adaptability. Using an empirical juridical qualitative approach with semi structured interviews conducted with four active Satreskrim personnel, the findings reveal an asymmetric capacity condition. HR capacity is relatively adequate for handling conventional crimes but faces serious gaps in dealing with contemporary criminal challenges, particularly digital based crimes. The study identifies structural factors contributing to integrity vulnerabilities, including budget shortfalls, supervisory weaknesses, and workload imbalances, that frame ethics violations not merely as individual failures but as systemic issues. Professionalism is demonstrated through procedural adherence, though constrained by excessive caseloads and training that does not fully address field realities. Adaptability is the most critically deficient dimension, with informal learning mechanisms insufficient to address rapidly evolving crime patterns. This study proposes a three layer HR capacity improvement strategy: reformed competency based recruitment, customized structured training (prioritizing digital forensics), and a strengthened integrity and accountability system including whistleblowing mechanisms and investigator welfare improvements.